Perlindungan Hukum terhadap Konsumen Pembeli Sewa dalam Perjanjian Beli Sewa di Indonesia - Aksar Aksar; Mulia Akbar Santoso; Miftahur Rachman; Umar Dinata; R Desril (SENTRI: Jurnal Riset Ilmiah, 2026)
The development of hire-purchase agreements in Indonesia has shown a significant increase; however, the bargaining position of consumers remains weaker than that of business operators, resulting in contractual imbalances, particularly in standard clauses that disadvantage consumers. This article examines the legal protection of consumers in hire-purchase agreements under Indonesian civil law and its practical implications. The research addresses two main questions: how consumer legal protection is regulated in hire-purchase agreements under Indonesian civil law, and what shortcomings exist in protecting consumers against unfair standard clauses. Using a normative legal research method with a literature study and qualitative analysis of relevant legal regulations, this study finds that although civil law upholds the principle of freedom of contract, consumer protection remains inadequate in practice. The most frequent violations of consumer rights are found in standard clauses that unilaterally shift risks to consumers, limit or exclude the liability of business operators, impose disproportionate penalties in cases of default, and restrict consumers’ rights to dispute resolution. These practices significantly weaken consumers’ legal position in hire-purchase agreements. Therefore, stricter supervision of standard clauses is necessary, along with more specific and clearer regulations to prevent abusive contractual practices. This study recommends strengthening regulatory frameworks to balance the bargaining position between consumers and business operators and enforcing stricter oversight of standard clauses in hire-purchase agreements.